2014
DOI: 10.1155/2014/196281
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in Psychoses

Abstract: Most individuals diagnosed with a mental illness are not violent, but some mentally ill patients commit violent acts. PubMed database was searched for articles published between 1980 and November 2013 using the combination of key words “schizophrenia” or “bipolar disorder” with “aggression” or “violence.” In comparison with the general population, there is approximately a twofold increase of risk of violence in schizophrenia without substance abuse comorbidity and ninefold with such comorbidity. The risk in bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 182 publications
(222 reference statements)
0
10
0
Order By: Relevance
“…People with personality disorder (PD) have similarly increased violence rates and this increases further if the diagnosis is antisocial PD (ASPD) [8]. Previous reviews have presented evidence supporting the efficacy of pharmacological treatments in reducing violence during psychosis [9, 10] but issues including non-adherence and non-response to anti-psychotic medications [11] and the aetiological heterogeneity of violence during psychosis [12] may limit the efficacy of pharmacological treatments across the spectrum of violent psychiatric patients and mentally disordered offenders (MDOs).…”
Section: Introductionmentioning
confidence: 99%
“…People with personality disorder (PD) have similarly increased violence rates and this increases further if the diagnosis is antisocial PD (ASPD) [8]. Previous reviews have presented evidence supporting the efficacy of pharmacological treatments in reducing violence during psychosis [9, 10] but issues including non-adherence and non-response to anti-psychotic medications [11] and the aetiological heterogeneity of violence during psychosis [12] may limit the efficacy of pharmacological treatments across the spectrum of violent psychiatric patients and mentally disordered offenders (MDOs).…”
Section: Introductionmentioning
confidence: 99%
“…Aggressiveness is strongly dependent on the type of disorder with which it is associated, as there are different disorders such as psychiatric disorders, neurological diseases, and personality disorders [34, 36]. Different studies have shown that psychopathic, psychotic symptoms and related factors relatively contribute to the development of aggressive behaviors [7]. In the field of suicidal behavior, major depression, impulsiveness, and aggressiveness are some of the main factors associated with suicide [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study reported that the rate of violent reoffending was lower during periods in which individuals were dispensed antipsychotics, psychostimulants, and drugs for addictive disorders [5]. Use of substances, such as alcohol and drugs, has been linked with a direct increase in risks of violent incidents in psychiatric patients [3, 6, 7]. Diehl et al [8] showed that violent crime was strongly associated with various sexual behaviors and the severity of substance dependence [8], which are clinical manifestations of positive valence systems [9].…”
Section: Introductionmentioning
confidence: 99%
“…In reality, violence in patients with schizophrenia is a frequent reason for hospitalization; it may delay hospital discharge and increases the illness burden carried by patients' families [6]. The severity of violent behavior in patients with schizophrenia is variable, and homicide may rarely occur [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For all these reasons, efforts to prevent or reduce violence in patients with schizophrenia are worthwhile. The origins of violence in patients with schizophrenia are heterogeneous, with different pathways leading to the same phenotype of violent behavior [6,9,10]. This heterogeneity of origin will be reflected in preventative efforts.…”
Section: Introductionmentioning
confidence: 99%